Operative Approaches to Nipple-Sparing Mastectomy Indications, Techniques, & Outcomes - Harness, Jay K.; Willey, Shawna C.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This text is designed to present a comprehensive overview of the evolution, oncologic safety, surgical approaches and outcomes of NSM. The book is targeted at general surgeons, dedicated breast surgeons, and plastic surgeons. There is focus for surgeons just beginning their use of NSM, as well as a review of patient selection criteria, operative approaches, reconstruction options, and management of complications. Chapters are written by experts in the performance and reconstruction of NSM. Chapters are supplemented with appropriate illustrations, and photos of NSM techniques and reconstructions. Operative Approaches to Nipple-Sparing Mastectomy: Indications, Techniques, & Outcomes will become a valuable resource for surgeons, including those in-training, who have a focus on state-of-the-art breast cancer surgery. .
The Evolution of Nipple-Sparing Mastectomy -- Nipple and Breast Anatomy -- Patient Selection and Breast Imaging -- The Inframammary Approach: The Georgetown Experience -- The Inframammary Approach: The UCSF Experience -- The Vertical Infra-Areolar Approach -- NSM in the Large Ptotic Breast -- NSM in the Community Hospital Setting -- Reducing Complications and Margin Issues with NSM -- Techniques to Avoid Nipple and Flap Necrosis -- Using the Breast Reconstruction Risk Assessment (BRA) Score -- Plastic Surgery Considerations in Reconstruction after NSM -- Acellular Tissue Matrices-To Use or Not? -- Pre-pectoral Reconstruction with Strattice -- Pre-pectoral Reconstruction without ADM -- NSM in the Previously Radiated Patient -- Experience with Post-Mastectomy Radiation Therapy in NSM -- Management of Complications after NSM -- Florescence Imaging in Breast Reconstruction: Minimizing Complications and Improving Outcomes -- The Science Behind Fat Grafting and ADMs -- The Team Approach to NSM and Reconstruction -- The Intraoperative Team Approach to NSM -- The American Society of Breast Surgeons NSM Registry.
Keywords: Medicine; Surgery; Plastic surgery; Medicine & Public Health; General Surgery; Plastic surgery